TEKNOLOGI PEMBENIHAN SEBAGAI UPAYA PELESTARIAN IKAN LOKAL (Tor spp) DI DESA KUTA TEUNGOH KECAMATAN BEUTONG BANGGALANG - Baihaqi Baihaqi; Husni Yulham; Afrizal Hendri (Universitas Teuku Umar, 2015)
IbM's activities in an effort to introduce and enrich the diversity of species in the family Cyprinidae genotip to the interests of farming and its derivatives. Because it needs to be done as well as the mastery of the production activity of hatcheries Beutong Ateuh from Sungai kerling. Given the genetic material contained in fish kerling, expected to be used to produce more eggs and seeds. So the guarantee the availability of these fish later, reducing the activity of the arrest from nature as well as support activities restoking, besides economic community could increase the local village. The approach used to address the issue of partners has provided the means to fish had seeded kerling/kerling fish produce seeds. The next technological transfers conducted pre-seeding (preparation of an indukan, an pendederan, a indukan fish preparation, manufacture and supply of kerling on-site hatchery), seeding (how to stem the kerling selection is ready to use for the production of seed, means injecting stem kerling, ways of stripping, how to determine the success of fertilization, larvae, maintenance ways how to seed until enlargement size ready to spread), post seeding (how good seed selection), as well as fish outfarm kerling (aspects of marketing : products/commodities, price, promotion, place/distribution). Ipteks activities for the community is quite helpful partners in preserving local fish germplasm kerling, this activity has been running 85%, including equipping facilities activities ipteks. But in terms of increased income partners the desired target is not reached, given the parent fish kerling used suffered the death of some tail. A good fish seed breeding is on a container that apply the system of running water.